Does Breastfeeding Protect Young Infants From Pertussis? Case-control Study and Immunologic Evaluation. Issue 3 (March 2017) - Pandolfi, Elisabetta; Gesualdo, Francesco; Carloni, Emanuela; Villani, Alberto; Midulla, Fabio; Carsetti, Rita; Stefanelli, Paola; Fedele, Giorgio; Tozzi, Alberto Eugenio
Abstract : Background: Pertussis infection can be severe in unvaccinated infants. A case-control study was conducted to investigate the potential role of breastfeeding in protecting young, unvaccinated infants from pertussis. Methods: Hospitalized infants <6 months of age with positive real time polymerase chain reaction for pertussis on nasopharyngeal aspirate were enrolled as cases; healthy controls were enrolled among patients admitted for ultrasound screening. Vaccinated infants were excluded. Sociodemographic, clinical and feeding information were collected. The effect of breastfeeding on pertussis was investigated through multivariable analysis. Breast milk and blood samples were obtained from mothers of patients. IgA and bacterial binding against Bordetella pertussis and other bacteria were tested in breast milk. IgG against pertussis toxin (PT) was tested in serum. Results: We enrolled 296 patients (61 cases and 235 controls). Exclusive breastfeeding was not associated with pertussis compared with partial breastfeeding/artificial feeding [odds ratio: 1.2; 95% confidence interval (CI): 0.31–4.67]. Children with siblings were at higher risk for pertussis (odds ratio: 2.5; 95% CI: 1.21–5.35). IgA against pertussis antigens were not higher in cases (IgA anti-PT median = 0.24 optical density) compared with controls (IgA anti-PT median = 0.21 optical density). Though bacterial binding to B. pertussis, measured in breast milk, was higher in cases (median = 4.35%) compared with controls (median = 2.8%; P = 0.004), bacterial binding to B. pertussis was low compared with other pathogens. IgG titers were higher in mothers of cases, but no correlation was found between serum IgG and breast milk IgA. Conclusion: Breastfeeding remains a mainstay of prevention for numerous diseases, though it does not seem to play a role against pertussis. Alternative strategies to protect unvaccinated infants from pertussis should be considered.